Preconditioning for thermal reservoir simulation - Roy, T; Roy, T (2019)
Multiphase flow through porous media can be modelled as a complex system of partial differential equations. Such models can be used to optimize the recovery of oil and gas from subsurface reservoirs. In the case of highly viscous oils, thermal recovery techniques are typically used to enhance their extraction. To simulate this, models describing the flow of fluids (typically oil, water, and gas) are coupled with a model for heat flow. Thermal reservoir simulation entails solving these highly coupled systems. Their complexity and the computational effort needed to solve them motivate the need for highly efficient solvers.